The Complete Chloroplast Genome Sequences of Three Veroniceae Species (Plantaginaceae): Comparative Analysis and Highly Divergent Regions - Choi, Kyoung Su; Chung, Myong Gi; Park, SeonJoo (Frontiers in Plant Science, 2016)
Previous studies of Veronica and related genera were weakly supported by molecular and paraphyletic taxa. Here, we report the complete chloroplast genome sequence of V. nakaiana and the related species V. persica and Veronicastrum sibiricum. The chloroplast genome length of V. nakaiana, V. persica and Veronicastrum sibiricum ranged from 150,198 bp to 152,930 bp. A total of 112 genes comprising 79 protein coding genes, 29 tRNA genes, and 4 rRNA genes were observed in three chloroplast genomes. The total number of SSRs was 48, 51 and 53 in V. nakaiana, V. persica and Veronicastrum sibiricum, respectively. Two SSRs (10 bp of AT and 12 bp of AATA) were observed in the same regions (rpoC2 and ndhD) in three chloroplast genomes. A comparison of coding genes and non-coding regions between V. nakaiana and V. persica revealed divergent sites, with the greatest variation occurring petD-rpoA region. The complete chloroplast genome sequence information regarding the three Veroniceae will be helpful for elucidating Veroniceae phylogenetic relationships.